Environmental degradation and its impact on the aesthetic view of the tourist natural resource in the Lattakia region Badrosieh resort - مخلوف هنادي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Most of the tourist sites with an aesthetic landscape suffer from the problems of environmental deterioration, which cause damages that threaten human health, environmental systems and the beauty of these sites, which leads to a disruption of the environmental balance between the various elements of the environment due to their inability to absorb this amount of degradation. It reaches the extent of affecting economic growth by affecting the natural ingredients and the various resources that are considered a source Important for attracting tourists and revitalizing tourism, which is one of the main pillars of the national economy, and from it the research deals with the negative impact of environmental degradation on distorting the aesthetic view of the specific tourist natural resources (Al-Badrousiya resort) and highlighting the importance of coastal and mountainous resorts, degradation of forests and pollution of the beach, as well as the risks resulting from quarries within its vicinity .